Vedic Astral Lore and Planetary Science in the Gārgīyajyotiṣa - Mak, Bill M. (History of Science in South Asia)

(untitled) (University of Alberta Library, 2019)
Among the sixty-four aṅgas of the large recension of the Gārgīyajyotiṣa (also known as the Gargasaṃhitā), celestial omens and planetary science (including astrology and narrative) occupy the greatest portion of the text. Some of these materials are widely cited later on in works such as Varāhamihira's Bṛhatsaṃhitā as well as Buddhist works such as the Śārdūlakarṇāvadāna and Amoghavajra's Xiuyao jing, and are considered some of the oldest sources of early, pre-siddhāntic Indian astral science. In this paper, I shall highlight some of the unique characteristics of the unedited chapters of the work where such materials are found, with focus on the planetary science and the methods of time-reckoning.